Deformation and failure modes of aluminum foam-cored sandwich plates under air-blast loading. (15th February 2021) - Li, Ying; Ren, Xianben; Zhang, Xiaoqiang; Chen, Yanfei; Zhao, Tian; Fang, Daining
Highlights: Experiment was conducted to investigate the ductile deformation and failure modes. 3D reverse scanning technique is adopted to obtain the deformation. Dimensionless expression and failure modes under effect of blast loading were obtained. Abstract: In this paper, air-blast experiments were firstly carried out to investigate the deformation and failure modes of aluminum foam-cored sandwich plates. The maximum midpoint deflection of the foam-cored sandwich plates was assessed by using a 3D scanning device considering the effects of different impulses. Failure modes of each components were analyzed. Based on that, a finite element model was proposed to verify the experimental results and to gain a further understanding of the air-blast process. It was found that: (1) there was a positive correlation between the maximum midpoint deflection of the rear plate and the revised dimensionless impulses; (2) the effects of the quasi-static air pressure should be taken into account in the short-distance blast resistance structural design; (3) the major failure modes of the core layer included large overall deformation, local compression, fragmentation and fly-out; (4) the failure modes of the face sheets mainly presented as large ductile deformation and petalling. (5) The energy absorption was mainly dominated by the foamed-core part.